Ann Street, Ballycastle - Dallat, Cahal; Federation of Local History Societies (Ireland); Federation for Ulster Local Studies (1990)
The Lawrence Photographic Project 1990/1991 was a project where one thousand photographs from the Lawrence Collection in the National Library of Ireland were replicated a hundred years later by a team of volunteer photographers, thereby creating a record of the changing topography of the selected locations.
Weather conditions noted by photographer: Fine
Film number: 6A ; frame number: 28
The only noticeable change in this street is the motor traffic. The area has been designated a conservation area by the DOE(N.I. )in May 1990.
Photograph taken at 17.15, 25 Sept, 1990
Ballycastle, County Antrim, Province of Ulster, Ireland.
surveyed
Keywords: Antrim (Northern Ireland : County) -- 1990-2000; Ballycastle (Antrim, Northern Ireland) -- 1990-2000; Photographic prints -- Ireland -- 1990-2000.